Open mesh repair of a voluminous recurrent inguinal hernia complicated by strangulation and intestinal obstruction - Edeh, Anthony Jude; Nwangwu, Chukwuemeka Chijioke; Okenwa, Wilfred Okwudili; Anekpo, Chijioke Chinedu; Eze, Balantine Ugochukwu Nicholas; Basil-Nwachukwu, Chinonso Chibueze (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Inguinal hernia is a common surgical pathology in Nigeria but a giant (voluminous) recurrent strangulated inguino-scrotal hernia causing intestinal obstruction is very uncommon. Such a hernia, when it is recurrent and becomes complicated with strangulation and dynamic intestinal obstruction, presents many difficulties in management. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To present the successful management of a case of a strangulated and obstructed giant recurrent inguinal hernia. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. Here we present the case of 47 year old man who had intestinal resection and anastomosis with prolene mesh repair of the posterior wall for a strangulated recurrent large inguinal hernia using the technique of tension free sutured prolene mesh popularized by Lichtenstein. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The patient recovered, was satisfied with his care and has been symptom free at 18 months of follow up. Giant recurrent hernias complicated by strangulated and intestinal obstruction are uncommon in Nigeria today, despite our resource-poor status. When they occur, tension free repair with sutured onlay prolene mesh after Lichtenstein, can be a useful and the best option with satisfactory results, as in the case reported.